2011
DOI: 10.4061/2011/257168
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Italian Obese Children and Adolescents: Stronger Association with Central Fat Depot than with Insulin Sensitivity and Birth Weight

Abstract: Aim. To evaluate whether body fat distribution, birth weight, and family history for diabetes (FHD) were associated with metabolic syndrome (MetS) in children and adolescents. Methods. A total of 439 Italian obese children and adolescents (5–18 years) were enrolled. Subjects were divided into 2 groups: prepubertal and pubertal. MetS was diagnosed according to the adapted National Cholesterol Education Program criteria. Birth weight percentile, central obesity index (measured by dual-energy X-ray absorptiometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 31 publications
0
30
0
2
Order By: Relevance
“…This finding suggests lipoperoxidation increases as IR worsens. Similarly, evidence of lipid peroxidation has been reported in a number of diabetic complications and significantly contributes to endothelial dysfunction, a key event in the pathogenesis of diabetic microvascular disease. Once oxidative stress appears, there is a cascade of events that predicts rapid disease progression and early development of complications.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This finding suggests lipoperoxidation increases as IR worsens. Similarly, evidence of lipid peroxidation has been reported in a number of diabetic complications and significantly contributes to endothelial dysfunction, a key event in the pathogenesis of diabetic microvascular disease. Once oxidative stress appears, there is a cascade of events that predicts rapid disease progression and early development of complications.…”
Section: Discussionmentioning
confidence: 80%
“…In this context, WC measurement offers incremental clinical utility above that of BMI in children. Likewise, WC and increased visceral fat deposits are strong, independent predictors of metabolic alterations (33).…”
Section: Discussionmentioning
confidence: 99%
“…BMI, WC, and WHtR correlate with the amount of visceral adipose tissue, although some studies have shown the WC to be the anthropometric measure that best correlates with the amount of visceral adipose tissue (44). Visceral adipose tissue is considered a risk factor for various metabolic disorders and cardiovascular risk at all stages of life (45)(46)(47). Insulin resistance and metabolic syndrome appear to increase the risk of asthma occurrence (48).…”
Section: Discussionmentioning
confidence: 99%
“…13. All seven papers which studied MetS 33,35,43,47,50,51,57 indicated that the risk of its incidence was higher in those born with LBW than in those of normal BW, and findings in four of them 33,43,51,57 were statistically significant. 14.…”
Section: Findings Related To the Barker Hypothesismentioning
confidence: 93%